2003
DOI: 10.1093/jac/dkg174
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus 1 replication in vitro by a self-stabilized oligonucleotide with 2'-O-methyl-guanosine-uridine quadruplex motifs

Abstract: The anti-HIV-1 activity of this oligonucleotide was increased when the phosphodiester and 2'-hydroxyl groups on the oligonucleotide backbones were replaced with a phosphorothioate and 2'-O-methyl backbone; thus Gm3Um4Gm3-s may inhibit HIV-1 infection, at least in part, by blocking the interaction between gp120 and CD4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To reduce possible background signals generated by nuclease activity, the probe was modified to contain 2’-OMe groups and phosphorothioate linkages. The combination of both modifications have been shown to increase resistance of oligonucleotides to nuclease activity [ 27 ]. In vitro tests confirmed that this nuclease-resistant probe (NR- 1 ) behaved similarly to the unmodified probe 1 (Figure D in S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…To reduce possible background signals generated by nuclease activity, the probe was modified to contain 2’-OMe groups and phosphorothioate linkages. The combination of both modifications have been shown to increase resistance of oligonucleotides to nuclease activity [ 27 ]. In vitro tests confirmed that this nuclease-resistant probe (NR- 1 ) behaved similarly to the unmodified probe 1 (Figure D in S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…36 In addition, phosphorothioate oligonucleotides were recently shown to block gp120 interactions and HIV infection in vitro. 49 Other viral infections were also targeted for aptamer intervention, including those owing to hepatitis C virus (HCV), Rous sarcoma virus and Human cytomegalovirus. Aptamers have been generated against the HCV proteins Nonstructural proteins 3 (NS3) and 5B (NS5B) that are required for viral proliferation.…”
Section: Aptamers For Intracellular Targets Are Being Developedmentioning
confidence: 99%
“…The use of modified chemistries in the thrombin binding aptamer have lead to higher stability(106,(128)(129)(130)(131)231,235), increased binding affinity(106,128), and enhanced biological activity(122,128,231,236,237), including studies in vivo. In a similar manner, studies involving modified nucleic acid chemistries have enhanced the properties of anti-HIV aptamers(106,123,230,(238)(239)(240)(241).…”
mentioning
confidence: 95%